TLC and the Fundamentalist Family: A Televised Quiverfull of Babies - Mesaros-Winckles, Christy (Journal of religion and popular culture, 2010)
The Quiverfull Movement has gained media attention in the United States due to the success of the The Learning Channel's show 19 and Counting. The movement believes children are a gift from God and that using any form of birth control goes against God's family planning. The subjection of women is also prevalent in the Quiverfull movement. Using a feminist perspective of televisual narrative analysis, I will examine four episodes from the show to argue that it provides a platform for legitimizing a radical Christian sect that oppresses basic human rights of the women who belong to the movement.